Factores socio- ecónomico y culturales de las adolescentes con amenaza de parto pretérmino que acuden al Hospital Regional Isidro Ayora de la ciudad de Loja, durante el periodo de junio a octubre del 2013. - Castro Delgado, Sonia Karina (2013)
This study whose theme is: SOCIO-ECONOMIC AND CULTURAL FACTORS OF TEENS WITH THREAT PRETERM REGIONAL HOSPITAL ATTENDING AYORA ISIDRO Loja CITY DURING THE PERIOD FROM JUNE TO OCTOBER 2013; where I set out to investigate the following objectives: Determine Risk Factors Socioeconomic, Demographic and Cultural Adolescents with APP. Determine gynecological and obstetric history, obstetric factors affecting the APP. Gestational age Identify which presents mostly the APP and establish the percentage of adolescents attending Prenatal Controls performed periodically. The results are as follows: Age at which more was presented APP is 17-19 years (52%), Secondary Education (66%) Status: Single (73%). Religion: Catholic (93,2%), From Urban (79.5%). Living Home Ownership (48%), living with Nuclear Family (57%), Occupation: Student (77%), Economic Income <$ 100 (45.5%). IVSA <15 years (68%), # Sex Partners: One (75%), UTI (66%), STI (27%), Age Gestation: 33.5-36.6 Weeks (59%). CPN:> 4 (70.5%) KEY WORDS: Preterm Threat, Risk Factors, Gestational Age.